How do patients with anorexia nervosa "process" psychotherapy between sessions? A comparison of cognitive–behavioral and psychodynamic interventions. (2nd November 2018) - Zeeck, A.; Hartmann, A.; Wild, B.; De Zwaan, M.; Herpertz, S.; Burgmer, M.; von Wietersheim, J.; Resmark, G.; Friederich, H.-C.; Tagay, S.; Dinkel, A.; Loewe, B.; et al.
Abstract: Objective: Patients' processing of psychotherapy between sessions ("inter-session process" (ISP)) has been repeatedly shown to be related to outcome. The aim of this study was to compare ISP characteristics of cognitive–behavioral vs. psychodynamic psychotherapy in the treatment of anorexia nervosa (AN) and their relation to outcome. Methods: Data of 106 patients participating in a randomized-controlled trial who received either 40 sessions of enhanced cognitive–behavioral therapy (CBT-E) or focal psychodynamic therapy (FPT) were analyzed. The ISP was measured with the Inter-session Experience Questionnaire (IEQ). Three outcome classes were distinguished: full recovery, partial recovery, and still fulfilling all AN criteria. Results: Patients receiving CBT-E reported more on "applying therapy" in the initial and the final treatment phase compared to FPT patients. In terms of process–outcome relations, higher levels of "recreating the therapeutic dialogue between sessions, " "recreating the therapeutic dialogue with negative emotions" as well as "applying therapy with negative emotions" in the final phase of treatment predicted negative outcome in FPT, whereas overall higher levels of negative emotions predicted negative outcome in CBT-E. Conclusions: In outpatient treatment in AN, the processing of therapy as measured by the IEQ showed surprisingly few differences between CBT-E and FPT. However, different ISP patterns were predictive of outcome, pointing to different mechanisms of change.